2007
DOI: 10.1534/genetics.107.074823
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Discovery and Classification of Candidate Ovarian Fertility Genes in the Mouse

Abstract: Female infertility syndromes are among the most prevalent chronic health disorders in women, but their genetic basis remains unknown because of uncertainty regarding the number and identity of ovarian factors controlling the assembly, preservation, and maturation of ovarian follicles. To systematically discover ovarian fertility genes en masse, we employed a mouse model (Foxo3) in which follicles are assembled normally but then undergo synchronous activation. We developed a microarray-based approach for the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 81 publications
10
77
0
Order By: Relevance
“…RNA preparation, microarray hybridization, normalization, quality control, and digital Northern analysis was performed as described previously (24). Additional data sets included in this analysis were intact PD2 testes and cultured SSCs established as previously described (61), both from FVB/n mice.…”
Section: Tm11fanmentioning
confidence: 99%
“…RNA preparation, microarray hybridization, normalization, quality control, and digital Northern analysis was performed as described previously (24). Additional data sets included in this analysis were intact PD2 testes and cultured SSCs established as previously described (61), both from FVB/n mice.…”
Section: Tm11fanmentioning
confidence: 99%
“…Having successfully employed this method for the systematic discovery of ovary-specific fertility factors (Gallardo et al, 2007b), we then applied the method to the mouse uterus, leading to the identification of five candidate genes. Subsequent analyses demonstrated that one of these genes, Sprr2f, was highly expressed in the uterus, but not in other tissues (Fig.…”
Section: Discovery Of Sprr2f As a Gene Expressed Only In Endometrial mentioning
confidence: 99%
“…To identify uterine-specific genes in the mouse, mouse uteri harvested on the day of estrus, and a panel of 13 other tissues, were profiled using Affymetrix 430 2.0 arrays exactly as described (Gallardo et al, 2007b). All data sets were normalized by global scaling, and each probe set in the array was ranked by the signal ratio of the uterine sample relative to the average of the 13 somatic tissues.…”
Section: Identification Of Sprr2f and Analysis Of Gene Expressionmentioning
confidence: 99%
“…[20][21][22][23] Although gene expression profile data for fetal or neonatal ovaries have been provided in mouse and human, and have enabled the analysis of genes involved in the initiation of meiosis, the sex differentiation of the gonad, early meiosis, and ovarian and follicle development, investigations of meiotic prophase I have been lacking. [24][25][26][27][28] In yeast, it is estimated that B150 genes may be meiosis-specific. 29,30 In our current study, we screened 99 genes that are upregulated during prophase in meiosis I.…”
Section: Discussionmentioning
confidence: 99%